2019
DOI: 10.1093/gastro/goz057
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous antral gastritis in relation to Helicobacter pylori infection, nutrition, and gastric atrophy

Abstract: Background There have been few studies in the English literature regarding verrucous gastritis (VG). The present study investigated the clinical and endoscopic features of verrucous antral gastritis, especially focusing on Helicobacter pylori infection, nutrition, and gastric atrophy. Methods We performed a retrospective study of patients who underwent routine endoscopy with indigo carmine chromoendoscopy and a comparative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Moreover, in VG, the lesions are arranged along longitudinal folds converging toward the pylorus ring. Tsuji et al [ 26 ] reported that Hp negativity was independently associated with VG regardless of the history of Hp eradication. Moreover, when endoscopic findings show flat elevated or depressed lesions, the differential diagnosis should include VG or early GC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in VG, the lesions are arranged along longitudinal folds converging toward the pylorus ring. Tsuji et al [ 26 ] reported that Hp negativity was independently associated with VG regardless of the history of Hp eradication. Moreover, when endoscopic findings show flat elevated or depressed lesions, the differential diagnosis should include VG or early GC.…”
Section: Discussionmentioning
confidence: 99%